PAR3 and aPKC regulate Golgi organization through CLASP2 phosphorylation to generate cell polarity - Matsui, Toshinori (Mol Biol Cell, 2015)
The organization of the Golgi apparatus is essential for cell polarization and its maintenance. The polarity regulator PAR complex (PAR3, PAR6, and aPKC) plays critical roles in several processes of cell polarization. However, how the PAR complex participates in regulating the organization of the Golgi remains largely unknown. Here we demonstrate the functional cross-talk of the PAR complex with CLASP2, which is a microtubule plus-end–tracking protein and is involved in organizing the Golgi ribbon. CLASP2 directly interacted with PAR3 and was phosphorylated by aPKC. In epithelial cells, knockdown of either PAR3 or aPKC induced the aberrant accumulation of CLASP2 at the trans-Golgi network (TGN) concomitantly with disruption of the Golgi ribbon organization. The expression of a CLASP2 mutant that inhibited the PAR3-CLASP2 interaction disrupted the organization of the Golgi ribbon. CLASP2 is known to localize to the TGN through its interaction with the TGN protein GCC185. This interaction was inhibited by the aPKC-mediated phosphorylation of CLASP2. Furthermore, the nonphosphorylatable mutant enhanced the colocalization of CLASP2 with GCC185, thereby perturbing the Golgi organization. On the basis of these observations, we propose that PAR3 and aPKC control the organization of the Golgi through CLASP2 phosphorylation.